Unplanned extubations in general intensive care unit: A nine-year retrospective analysis - Lucchini, Alberto; Bambi, Stefano; Galazzi, Alessandro; Elli, Stefano; Negrini, Cristina; Vaccino, Stefania; Triantafillidis, Silvia; Biancardi, Alessandra; Cozzari, Mattia; Fumagalli, Roberto; Foti, Giuseppe (Acta bio-medica : Atenei Parmensis, 2018)
Unplanned extubation (UE) in Intensive Care Units (ICU) is an indicator of quality and safety of care. UEs are classified in: accidental extubations, if involuntarily caused during nursing care or medical procedures; self-extubation, if determined by the patient him/herself.  In scientific literature, the cumulative incidence of UEs varies from 0.3% to 35.8%. The aim of this study is to explore the incidence of UEs in an Italian university general ICU adopting a well-established protocol of tracheal tube nursing management and fixation. retrospective observational study. We enrolled all patients undergone to invasive mechanical ventilation from 1st January 2008 to 31st December 2016. in the studied period 3422 patients underwent to endotracheal intubation. The UEs were 35: 33 self extubations (94%) and 2 accidental extubations (6%). The incidence of UEs calculated on 1497 patients intubated for more than 24 hours was 2.34%. Instead, it was 1.02%, if we consider the whole number of intubated patients. Only in 9 (26%) cases out of 35 UEs the patient was re-intubated. No deaths consequent to UE were recorded. The incidence of UEs in this study showed rates according to the minimal values reported in scientific literature. A standardized program of endotracheal tube management (based on an effective and comfortable fixing system) seems to be a safe and a valid foundation in order to maintain the UE episodes at minimum rates.